Paeoniflorin in Paeoniaceae: Distribution, influencing factors, and biosynthesis - Zhang, Xiao-Xiao; Zuo, Jia-Qi; Wang, Yi-Ting; Duan, Hui-Yun; Yuan, Jun-Hui; Hu, Yong-Hong (Frontiers in Plant Science, 2022)
Paeoniflorin, a monoterpene glucoside, is increasingly used in the clinical treatment of many diseases because it has a variety of pharmacological activities. Besides, paeoniflorin has been considered the characteristic chemical constituent of Paeoniaceae plants since it was first reported in 1963. Therefore, how to better develop and utilize paeoniflorin in Paeoniaceae has always been a research hotspot. We reviewed the current knowledge on paeoniflorin in Paeoniaceae, with particular emphasis on its distribution and influencing factors. Moreover, the limited understanding of the biosynthesis pathway has restricted the production of paeoniflorin by synthetic biology. This review provides insights into the post-modification pathway of paeoniflorin biosynthesis and proposes directions for further analysis in the future.